Water-heat balance characteristics of the sewage sludge bio-drying process in a full-scale bio-drying plant with circulated air. (15th March 2022) - Yu, Bao; Chen, Tongbin; Zheng, Guodi; Yang, Junxing; Huang, Xue; Fu, Lili; Cai, Lu
Graphical abstract: Highlights: Increased ventilation had no positive effect on the water removal of sludge bio-drying. Ventilation and pile temperature jointly determine the dehydration effect. More than 30% of the water was removed during the non-ventilation process. High ventilation obtained higher heat utilization efficiency with less energy input. Air circulation achieved energy recovery but carried more water into the pile. Abstract: Sewage sludge bio-drying technology has attracted considerable attention in recent years. In this study, we explored the water-heat balance under two ventilation strategies for the first time in bio-drying plants with circulated air, and examined the influence of air circulation on water removal and heat recovery. We want to obtain the relationships of pile temperature, ventilation, and water removal. Then, it provides support for optimizing the bio-drying process conditions and improving the efficiency through analysis of the water-heat relationship. In the low-ventilation and high-ventilation trials, water removed was mainly on Days 9–12 and 1–4, respectively. Ventilation and pile temperature jointly determine the water removed during the bio-drying process. Water balance indicated that more than 30% of the water was removed under the nonventilated process. More organic matter was degraded to maintain a higher pile temperature under low-ventilation than under high-ventilation, which also led to more radiation heat being lost. High-ventilation trial input less energy (3.36 MJ/kg water removed) but obtained a higher bio-drying index I (7.04) and heat utilization efficiency Q effic (94.1%). Heat balance showed that lower energy consumption by dry air ( Q dryair ) was obtained due to circulation air with high temperature. Circulation air also has a higher carried capacity of water vapor but carries more water into the pile due to higher humidity.